An examination of the potential of STEM-based biology learning for improving higher order thinking skills - Rahmawati, Dini Nurani; Surtikanti, Hertien Koosbandiah; Riandi, Riandi (Department of Biology Education, Universitas Pendidikan Indonesia, 2024)
In 21st-century learning, Higher Order Thinking Skill is a skill that is targeted to be possessed by students, because learning in biology has led to finding solutions to real problems faced by students that require reasoning and analysis to understand them. The purpose of this literature review is to determine the potential of learning with the STEM approach to increase HOTS. The research method used is a systematic literature review of several reputable articles published in recent years through content analysis. From the articles used in this review, it was found that there is an increasing trend of research variations in various learning methods. This study also shows that Environmental Change is the most widely used topic in STEM-related research, both at the high school and university levels. Concerning the findings of this study, several recommendations have been put forward for future research underpinning the STEM approach as the main focus in improving HOTS. Some of these recommendations include increasing the variety of research types and selecting more diverse biology topics.